ANALYSIS OF COMMUNITY'S WILL AND WANT TO USE FUEL WOOD IN DILI CITY, TIMOR LESTE - Freitas , Joao da Costa (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Firewood as traditional energy source are used by community in rural area. Firewood problems need serious attention and it is necessary to do the research about firewood. because 80% of the rural area in Timor Leste still using firewood as an energy sources. This research was conducted in May-June 2014 at Becora village, Lahane Oriental village, and Comoro village as targetted villages. The objectives of the study were to identify prespectives of community of Dili city on firewood consumption and activities of community in Dili city using firewood as priority energy. This study were using interview method and questionaire’s filling to respondents on the three targetted villages. Results of this study showed that community at Becora village, Lahane Oriental village, and Comoro village use firewood as an energy sources priority for household consumption. Firewood which utilizes by community were taken from natural forests in Timor Leste, and the precentage of common used species Ampupu woods 80%, Asam woods 5%, Kesambi woods 5%, Bakau woods 5%, and Lamtoro woods 5%.